Effect of process parameters for wire EDM of AISI H13 tool steel. (2022) - Divya Sadhana, A.; Udaya Prakash, J.; Ananth, S.; Jebarose Juliyana, S.; Sarala Rubi, C.
Abstract: Traditional machining processes struggle to machine materials with extremely high hardness. As a result, novel machining techniques such as ECM, USM and EDM have been developed for machining these materials. The Wire EDM process parameters of AISI H13 tool steel are optimized in this research using an effective approach. Gap Voltage, Pulse On Time, Pulse Off Time and wire feed are the input machining parameters used in the present work to achieve the highest MRR and lowest SR. The response table and response graphs were used to define the ideal levels of machining parameters. The significance of the machining parameters was decided by means of ANOVA. The greatest statistical effect on MRR is Gap Voltage (90.75%), other factors are not significant. The greatest statistical effect on SR is Gap Voltage (67.05%), followed by pulse off time (19.62). The confirmation experiments indicated that it is possible to increase the material removal rate and decrease the surface roughness by the proposed statistical technique.